Access to a Nutritious Diet in Samoa: Local Insights. Issue 3 (4th May 2019) - Farrell, Penny; Thow, Anne Marie; Schuster, Suzie; Vizintin, Pavle; Negin, Joel
ABSTRACT: The adult obesity prevalence in Samoa is the third highest globally, and diet is a significant contributor. Our study aimed to explore the behavioral and demographic factors which influence diets in Samoa. The most important findings for strategic policy design were: i) cost was the most important reason for food choice, ii) participants reported high rates of consumption of sugary and fatty energy foods – along with high rates of food insecurity, and iii) the food frequency questionnaire findings from our small sample are in line with the existing evidence that the nutrition transition is underway in Samoa.